Cybercrime Threat Landscape amid the Movement Control Order in Malaysia - Tharshini, N. K.; Zamri, Hassan; Faizah, Haji Masud (Faculty of Economics and Business, 2021)
The COVID-19 pandemic has evolved rapidly and affected almost all the world's countries, creating unprecedented chaos on human lives, physical health, mental wellbeing, and the world economy. During this time, digital space has become an indispensable global means of communication, entertainment, and social interaction. However, high reliance on digital tools increases the risk of being prey to cyberattacks. In order to explore the cybercrime threat landscape, empirical research was conducted to examine the shared experiences related to cybercrime threats during the enforcement of the Movement Control Order in Malaysia. Data was collected using an online survey among 332 respondents across Malaysia. The finding stipulated that most of the respondents comprised females aged between 18 and 28 years old. The result also indicated that majority of female became victims of online phishing/malware distribution [(M = 0.58, SD = 0.13); t (113) = 2.24, p = 0.02] and online sexual harassment [(M = 0.56, SD = 0.11); t (107) = 2.38, p = 0.01]. The understanding of cybercrime experiences faced by the public during MCO is essential to help law enforcement agencies to stay vigilant on issues related to public sa